FAKTOR PENGHAMBAT BERDIRINYA KOPERASI DI KELURAHAN GONDORIO KECAMATAN NGALIYAN KODIA SEMARANG - Yuyarti Yuyarti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The goal of this research is to reveal factors hindering the establishment of cooperation as an institution at the village of Gondoriasub-district Ngaliyan in Semarang. The approach used is descriptive qualitative and the methods for data collecting used in this researchare questionnaires and interviews. Questionnaires are used to find out the hindering factors in establishing the cooperation, and interviews are used to complete the information if there were the lackness of the data or to get the deep impression from the people. The results of the statistical analysis show that the members knowledge on cooperation is very low, ie. 53,3%. This is caused by the fact that in general they have low education and they do not know the meaning of cooperation, the base of cooperation, and the ideal of cooperation.